Software Architecture and Desgin for Online Registration System (The International Journal of Engineering & Information Technology (IJEIT), 2024)
This paper presents an example of SoftwareArchitecture and design for online registration system.Software design is an early phase of the Software DevelopmentLife Cycle (SDLC). During this phase, software designersmodel the system and assess its quality so that improvementsmay be made before the software goes into the productionphase. The goal of software design is to build a model thatmeets all customer requirements and leads to successfulimplementation. As software systems continue to grow inscale, complexity, and distribution, their proper designbecomes extremely important in software production. Thearchitecture design representat ion is derived from the systemrequirement specification and the analysis model. Multi tierarchitecture is commonly used for distributed systems. Itusually consists of three element types: client, middlewareserver, and data server. The Unified Modeling Language( used to model the problem domain; describe the userrequirements; identify significant architecture elementsduring software design, such as classes and objects; describebehavior and interactions among these elements; and organizethe softw are structure, specify its constraints, describe thenecessary attributes, and more.